Analisis Pengaruh Green Financing Terhadap Kinerja Keuangan Bank Umum Syariah Di Indonesia (2021-2024) - Laila Rahmayuni Rangkuti; Anggraini, Tuti; Nasution, Juliana (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of green financing on the financial performance of Sharia Commercial Banks in Indonesia, measured by Return on Assets (ROA), Return on Equity (ROE), and Non-Performing Financing (NPF). Using panel data from Sharia Commercial Banks during 2021–2024, the study applies a quantitative approach and panel data regression analysis with EViews. The findings reveal that green financing significantly affects financial performance. Specifically, green financing has a negative and significant impact on ROA, ROE, and NPF. These results suggest that while increased green financing may reduce profitability, it also contributes to lower financing risk and improved asset quality. Keywords: Green Financing; Financial Performance; ROA; ROE; NPF; Islamic Commercial Banks